2008
DOI: 10.1159/000151241
|View full text |Cite
|
Sign up to set email alerts
|

Different Atrophic Patterns in Early- and Late-Onset Alzheimer’s Disease and Evaluation of Clinical Utility of a Method of Regional z-Score Analysis Using Voxel-Based Morphometry

Abstract: Background/Aims: We evaluated the differential patterns of brain atrophy in early- and late-onset Alzheimer’s disease (AD) by measuring regional z-scores of voxel-based morphometry and assessed the availability of the method for clinical use. Methods: The first 50 patients with probable AD were compared to 83 age-matched control subjects to identify the brain atrophy. Regions of interest were set in the areas showing z-scores >4. To find substantial differences in the atrophy pattern, principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 64 publications
4
23
1
Order By: Relevance
“…In line with earlier studies (Cho et al, 2013)(Shiino et al, 2008, van de Pol et al, 2006, Whitwell et al, 2012), we found a more severe hippocampal and amygdala atrophy in LOAD than EOAD when compared to their controls. Local distribution of amygdala tissue reduction in EOAD mapped to the Ce, Aco and Pco nuclei.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with earlier studies (Cho et al, 2013)(Shiino et al, 2008, van de Pol et al, 2006, Whitwell et al, 2012), we found a more severe hippocampal and amygdala atrophy in LOAD than EOAD when compared to their controls. Local distribution of amygdala tissue reduction in EOAD mapped to the Ce, Aco and Pco nuclei.…”
Section: Discussionsupporting
confidence: 93%
“…Anatomically, this profile suggests a somewhat more localized disease affecting the medial temporal lobe (MTL) regions (Sa et al, 2012, Smits et al, 2012), (Reid et al, 1996), while the clinical profile of EOAD suggests broader neocortical involvement. These clinical observations are supported by in vivo magnetic resonance imaging (MRI) studies (Frisoni et al, 2005), (Frisoni et al, 2007),(Anonymous , Cho et al, 2013, Ishii et al, 2005, Karas et al, 2007, Moller et al, 2013, Shiino et al, 2006, Shiino et al, 2008, van de Pol et al, 2006, van der Vlies et al, 2013) and by recent pathological evidence (Whitwell et al, 2012). These findings support the view that MTL damage is a key neurological substrate in LOAD.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, because the PiB-negative dementia group was apparently free of amyloid deposition, the identification of other factors involved in the interruption of the default mode network is needed. Recent studies have demonstrated that precuneus atrophy is a characteristic of early-onset AD [22,23]. However, this finding was not supported in the present study because the PiBnegative dementia group did not include young patients.…”
Section: Discussioncontrasting
confidence: 85%
“…A Z-score relative to the normal database is then usually used to express the degree of atrophy in EC (Hayashi et al, 2012). The process is semiautomated, bias-free, and less time-consuming, and it enables a rapid and extensive survey of brain pathology (Shiino et al, 2008). VSRAD-confirmed temporal lobe atrophy in AD was reported to be more accurate than ROI-based analysis for discriminating mild to moderate AD patients from controls (Ashburner and Friston, 2000;Du et al, 2004;Testa et al, 2004).…”
Section: Voxel-based Specific Regional Analysis System For Admentioning
confidence: 99%